Major individual and regional variations in unit entrainment by oscillations of different frequencies - Mohamed Badawy; Ian T. Kim; Alon Amir; Mohammad M. Herzallah; Luisa F. Gomez-Alatorre; Drew B. Headley; Denis Paré (Scientific Reports)
Abstract In vitro studies have shown that a neuron’s electroresponsive properties can predispose it to oscillate at specific frequencies. In contrast, network activity in vivo can entrain neurons to rhythms that their biophysical properties do not predispose them to favor. However, there is limited information on the comparative frequency profile of unit entrainment across brain regions. Therefore, this study aimed to characterize the frequency profile of unit entrainment in cortex, thalamus, striatum, and basolateral amygdala (BLA) in rats of either sex. Neurons recorded simultaneously in a given brain region and behavioral state generally had very similar frequency profiles of unit entrainment. While cortical, striatal, and thalamic neurons were more strongly entrained by low than high local field potential (LFP) frequencies, increases in the power of these oscillations were linked to decreased firing rates for low frequencies versus increased firing rates for high frequencies. Deviating from this general trend, BLA neurons were more strongly entrained by high gamma than all other frequency bands in all subjects and states. By contrast, neurons in other regions displayed marked inter-individual variability. That is, although neurons in some regions had exceptionally high entrainment values in particular frequency bands, these were not observed consistently across rats. Based on these findings, some might infer that oscillations play a minor role or that different oscillatory patterns can support the same functions. Alternatively, the oscillations critical to brain function could be those not investigated here, namely those arising transiently in response to specific task variables or contexts. Perhaps those are less susceptible to genetic variations. While our findings do not allow us to determine which explanation is correct, they do highlight the perils of averaging.